2011
DOI: 10.17221/140/2011-cjgpb
|View full text |Cite
|
Sign up to set email alerts
|

Identification of apple scab and powdery mildew resistance genes in Czech apple (Malus × domestica) genetic resources by PCR molecular markers

Abstract: Abstract:The presence of genes for resistance to scab (Venturia inaequalis) and powdery mildew (Podosphaera leucotricha) was studied using molecular markers in a sample of 279 apple cultivars from the Czech collection of apple genetic resources. The sample comprised 37 cultivars supposed to have the Vf gene for scab resistance, 97 reference world cultivars and 145 old and local cultivars. Six PCR molecular markers for the scab resistance genes Vf, Vm, Vbj, Vr and Vh and three PCR molecular markers for the powd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 19 publications
1
10
0
2
Order By: Relevance
“…Roem., отдельные экотипы которой характеризуются присутствием в геноме гена Rvi4 (Savel'ev et al, 2016). В проведенном ранее в Чехии (Patzak et al, 2011) и Беларуси (Urbanovich, Kazlovskaya, 2008) скрининге генетической коллекции яблони (93 и 130 форм) ген Rvi4 идентифицирован у 32,3% и 26,1% генотипов соответственно.…”
Section: результаты и обсуждениеunclassified
“…Roem., отдельные экотипы которой характеризуются присутствием в геноме гена Rvi4 (Savel'ev et al, 2016). В проведенном ранее в Чехии (Patzak et al, 2011) и Беларуси (Urbanovich, Kazlovskaya, 2008) скрининге генетической коллекции яблони (93 и 130 форм) ген Rvi4 идентифицирован у 32,3% и 26,1% генотипов соответственно.…”
Section: результаты и обсуждениеunclassified
“…SCAR marker was also used by Bus et al, (14) for detection of apple scab resistance gene. Apple scab and powdery mildew resistance genes were detected in Czech apple cultivars (13) . AFLP-derived SCAR was applied by Huaracha et al, (22) in order to narrow down the region of the Vf locus for scab resistance gene in apple.…”
Section: Results and Discutionsmentioning
confidence: 99%
“…The first molecular markers related to the apple resistance gene Vbj (apple scab resistance gene) originating from the crab apple M. baccata jackii were presented by (12). Breeding programs were enriched when resistant genes tos-cab and powdery mildew identified in Czech apple (13) .A new apple scab resistance gene VT57 have been identified from Golden Delicious or Red Dougherty (14). HcrVf type candidate genes have been also identified in a range of Malus cultivars using sequence information from the cloned HcrVf genes (receptor-like protein) (15).…”
Section: Introducctionmentioning
confidence: 99%
“…The presence of genes for Scab and powdery mildew was studied using the molecular markers in 279 apply cultivars. (Patzak et al , 2011) also concluded that molecular makers are very powerful tools for the identification of presence of resistance genes.…”
Section: Discussionmentioning
confidence: 99%